Learning from South Sumatran indigenous technology for sustainable housing construction - Ari Siswanto (2013)
Nowadays, much local knowledge about South Sumatran traditional architecture is gradually disappearing because of the way of thinking and cultural changes in society. The introduction of new technology and building materials in the housing construction industry has made it possible for problems to be solved almost instantly. As a result, there has been a tendency to discard the traditional construction techniques that have been in use for centuries.. However, for generations, local communities have used such traditional indigenous building construction technology in traditional houses that were adapted to Nature and have withstood natural disasters. It would be an enormous lost for the community and country if such traditional skills, .expertise and problem solving strategies inherent in indigenous building construction were to be discarded and be lost forever. The objective of this research is to show that there can be many aspects of building construction that can be learned and developed from the indigenous technology of South Sumatran traditional architecture for sustainable housing construction This research uses a qualitative approach for its data collection through multiple-case study. The three strategies of analysis implemented in this research emphasise more description, comparison, and evaluation. The method used in this study comprised interviews, observation and visual documentation. Objects under study amounted to 13 traditional houses located in two cities and four regencies in a province of South Sumatra. Traditional houses were chosen based on previous research, information and field work. In addition, the determination of a traditional house is based on its geographical location and architectural style. The 29 respondents comprised owners or occupants of the houses studied, local leaders, community leaders, local builders and experts. Indigenous technology shows how site selection, house layout, structure and local materials of traditional houses have the ability to be environmentally friendly and able to withstand natural disasters for generations. Traditional houses are also very durable in the face of natural disasters such as landslides, floods and earthquakes. Proper understanding and interpretation of indigenous technology of traditional architecture that adapts to the environment can provide better housing solutions. Indigenous technology of South Sumatra’s traditional architecture can be interpreted as a concept for sustainable housing construction that is imbued with a sense of aesthetics, is environmentally friendly, utilizes logical technology, and in line with cultural and economic needs.